Effect of High Ratio of n-6/n-3 PUFAs on Depression: A Meta-Analysis of Prospective Studies - Wang, Yuanyuan; Dong, Lirong; Pan, Da; Xu, Dengfeng; Lu, Yifei; Yin, Shiyu; Wang, Shaokang; Xia, Hui; Liao, Wang; Sun, Guiju (Frontiers in Nutrition, 2022)
Objective: The aim of this systematic review and meta-analysis was to examine the association between high ratio of n-6/n-3 polyunsaturated fatty acids (PUFAs) and depression. Methods: The authors conducted a meta-analysis of research articles on the association of high ratio of n-6/n-3 PUFAs with the risk of depression published in the online article database on PubMed, Embase, Cochrane library as of December 2021. Pooled odds ratios (OR) were calculated using random effects models. Publication bias was assessed visually by funnel plots and statistically by the Egger’s and Begg’s tests. Data were processed using Stata version 16.0 (Stata Corporation). Results: This study reviewed 5739 articles. There were 12 studies included in this systematic review and meta-analysis with a total of 66,317 participants (including 4173 individuals with depression condition). The pooled results showed that high ratio of n-6/n-3 PUFAs might be positively correlated with depression [OR=1.21, 95% confidence intervals (CIs): 1.04~1.41]. The I2 test indicated that there was a substantial statistical heterogeneity across the included trials (I2 = 54.38%, P = 0.01). Subgroup analysis showed that high ratio of n-6/n-3 PUFAs in blood had no significant association with depression (OR=1.15, 95%CI: 0.88~1.50), while high ratio of n-6/n-3 PUFAs in dietary supplements was positively associated with depression (OR=1.32, 95%CI: 1.16~1.51). Conclusions: This meta-analysis confirmed the association between high ratio of n-6/n-3 PUFAs and the risk of depression. High ratio of n-6/n-3 polyunsaturated fatty acids in dietary supplementation were positively associated with depression, but had no significant association in the blood. This study suggested that lowering the dietary intake of n-6/n-3 polyunsaturated fatty acids would be beneficial in the prevention of depression.